Selective Protection of Alcohols as 2-Tetrahydropyranyl Acetals Using Keggin H3PW12O40 Effect of Different Reaction Parameters - Tayebee, Reza; Mahdavi, Behnam (Asian Journal of Chemistry, 2010)
Selective protection of some industrially and pharmaceutically important chemicals bearing primary and secondary hydroxyl groups were achieved using 3,4-dihydro-2H-pyran (DHP) as the protecting group by the presence of Keggin H3PW12O40 as catalyst. Findings revealed only protection of the primary alcoholic group in good yields. Different reaction parameters affecting efficiency of the formation of 2-tetrahydropyranyl acetals from alcohols catalyzed by H3PW12O40 were also studied. Characteristic reaction conditions include short times and room temperature.